Evaluating Economic Outcomes: Single-Use Aspirin vs. Aspirin-Clopidogrel in Ischemic Stroke Patients Based on Barthel Index Scores - Yosmar, Rahmi; Febiana, Dian; Fitria, Najmiatul (Fakultas Farmasi Universitas Andalas, 2023)
Ischemic stroke is a catastrophic disease that causes large costs in Indonesia. The high prevalence of stroke results in increased morbidity and mortality rates, which will impact the socioeconomic status of stroke patients. Cost Effectiveness Analysis (CEA) is a method in pharmaco-economics that aims to make decisions regarding the rational choice of therapy and evaluate the economic impact on ischemic stroke patients. This study aims to determine the Incremental Cost Effectiveness Ratio (ICER) value of antiplatelet therapy in the aspirin-clopidogrel combination group and the single aspirin group in ischemic stroke patients treated at the Regional General Hospital. Dr. M. Djamil Padang. The clinical parameter observed was the Barthel Index (BI) value. This research is a descriptive study with retrospective data collection using medical record data and the Hospital Management Information System (SIMRS) at RSUD Dr. M.Djamil Padang. The cost data shows the total direct medical costs incurred in treating ischemic stroke. Based on the results obtained, the Incremental Cost Effectiveness Ratio (ICER) value is IDR (-) 401,302. 71 per 1% increase. In this study it can be concluded that the aspirin-clopidogrel combination has better cost effectiveness than aspirin alone.